2023
DOI: 10.3389/fpubh.2023.1058026
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to pay for hepatitis B virus vaccine and associated factors among households in Bahir Dar City, northwest Ethiopia: using contingent valuation method

Addis Aychew,
Amare Minyihun,
Chalie Tadie Tsehay
et al.

Abstract: BackgroundThe prevention of disease burden and death through vaccination is one of the most cost-effective methods. Even though the Hepatitis B Virus (HBV) has significant public health problems in Ethiopia, there is no compulsory HBV vaccination program for adults and the vaccine's market value was not yet estimated in the Ethiopia context. Therefore, this study aimed to assess the willingness to pay (WTP) for the HBV vaccine and its associated factors among households in Bahir Dar City, northwest Ethiopia.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The proportions of anti-HBs concentration (100 ≤ anti-HBs < 1000 mIU/ml) in the 10 μg HP-10 μg HP and 20 μg CHO-20 μg CHO groups gradually increased, further demonstrating that the antibody levels of anti-HBs derived from 20μg HepB-CHO were superior to those from 10μg HepB-HP, consistent with the above study. Research has shown that working on attitudes and knowledge about the vaccine could potentially increase household willingness to pay for HepB ( 27 ). 20μg HepB-CHO was a self-pay vaccine, and 85.83% of children in our study received 20μg HepB-CHO at the Kecheng vaccination clinic, which was associated with improved attitudes and knowledge about vaccines in the main urban area of Kecheng district.…”
Section: Discussionmentioning
confidence: 99%
“…The proportions of anti-HBs concentration (100 ≤ anti-HBs < 1000 mIU/ml) in the 10 μg HP-10 μg HP and 20 μg CHO-20 μg CHO groups gradually increased, further demonstrating that the antibody levels of anti-HBs derived from 20μg HepB-CHO were superior to those from 10μg HepB-HP, consistent with the above study. Research has shown that working on attitudes and knowledge about the vaccine could potentially increase household willingness to pay for HepB ( 27 ). 20μg HepB-CHO was a self-pay vaccine, and 85.83% of children in our study received 20μg HepB-CHO at the Kecheng vaccination clinic, which was associated with improved attitudes and knowledge about vaccines in the main urban area of Kecheng district.…”
Section: Discussionmentioning
confidence: 99%